MAPPING THE EVOLUTION AND CURRENT TRENDS ISLAMIC FINANCE: BIBLIOMETRIC ANALYSIS - Budi Nur Siswanto (Al-Idarah, 2023)
This bibliometric analysis aims to map research on Islamic finance. The data source is taken from the Scopus database, with the subject matter of Economics and business, from the search for the word "Islamic finance" or "Islamic finance" and in English, the searched for articles that have been finally published. From the results of the data analysis in can be 1,438 articles, and analyzed. The results showed a significant increase in the number of research publications starting in 1996, and Malaysia as the country that published the most articles on Islamic finance. The most dominant keywords used are presented by VOSViewer, there are 8 Clusters consisting of: The terms "Islamic finance," "Sukuk," "Islam," "Islamic Bank," "Islamic banking," "Islamic financial services," "Sharia compliance," and "Financial crisis"